2007
DOI: 10.1021/jf062186c
|View full text |Cite
|
Sign up to set email alerts
|

Sorption Behavior of Mixtures of Glycerol and Starch

Abstract: Glycerol is often added to starches to plasticize the product, but the presence of glycerol may also affect the water content of the samples. To evaluate the effect of glycerol on the sorption properties of starches, waxy maize, rice, and wheat starch were thermomechanically extruded in the presence of glycerol. Sorption isotherms of these extruded samples were ascertained using dynamic vapor sorption (DVS). BET and GAB modeling showed a monolayer (mo) significantly higher for waxy maize than for rice and whea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
36
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 27 publications
7
36
0
1
Order By: Relevance
“…A maximum D eff value was observed at a w = 0.7, where the equilibrium moisture content was 0.18 g g −1 d.b. This typical bell-like curve for D eff values as a function of a w is in agreement with other studies (Enrione et al, 2007;Hanson, Cramer, Abraham, & Lancaster, 1971;Karathanos, Villalobos, & Saravacos, 1990;Yu, Schmidt, Bello-Perez, & Schmidt, 2008). Yu et al (2008), using the same method of water sorption kinetic than that used in this study, reported a maximum value of D eff in dent corn starch granules (30% of crystallinity) at 0.5 a w and significantly lower values for a w < 0.5 and >0.5.…”
Section: Apparent Diffusivity Of Watersupporting
confidence: 93%
See 4 more Smart Citations
“…A maximum D eff value was observed at a w = 0.7, where the equilibrium moisture content was 0.18 g g −1 d.b. This typical bell-like curve for D eff values as a function of a w is in agreement with other studies (Enrione et al, 2007;Hanson, Cramer, Abraham, & Lancaster, 1971;Karathanos, Villalobos, & Saravacos, 1990;Yu, Schmidt, Bello-Perez, & Schmidt, 2008). Yu et al (2008), using the same method of water sorption kinetic than that used in this study, reported a maximum value of D eff in dent corn starch granules (30% of crystallinity) at 0.5 a w and significantly lower values for a w < 0.5 and >0.5.…”
Section: Apparent Diffusivity Of Watersupporting
confidence: 93%
“…for high a w values. These values were in accordance with those obtained by Enrione, Hill, and Mitchell (2007) on extruded wheat starch containing 20% of glycerol (EMC 0.43 g g −1 against 0.53 g g −1 d.b. in this study at 0.9 a w ).…”
Section: Water Sorption Isothermsupporting
confidence: 91%
See 3 more Smart Citations